2001
DOI: 10.1253/jcj.65.60
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience With Nifekalant Hydrochloride (MS-551), A Novel Class III Antiarrhythmic Agent, in Patients With Acute Extensive Infarction and Severe Ventricular Dysfunction

Abstract: It has the unique characteristic of potent, nonselective K + channel blocking without inhibiting either the Na + channels or the -adrenergic receptors. In canine models of myocardial infarction, NIF effectively suppressed ventricular tachyarrhythmia, without compromising hemodynamics. 2,3 We report our initial experience of using NIF in patients with acute extensive infarction and severe ventricular dysfunction.Four male patients (age, 67±10 [mean ± SD] years) were referred because of extensive anterior acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 8 publications
3
23
0
1
Order By: Relevance
“…Takenaka, et al 19) reported that nifekalant is effective in treating malignant ventricular tachyarrhythmia following AMI with severe ventricular dysfunction that is refractory to class Ia and Ib antiarrhythmic agents. In another report, Igawa, et al showed that nifekalant could be an alternative drug for suppression of VT in patients with OMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takenaka, et al 19) reported that nifekalant is effective in treating malignant ventricular tachyarrhythmia following AMI with severe ventricular dysfunction that is refractory to class Ia and Ib antiarrhythmic agents. In another report, Igawa, et al showed that nifekalant could be an alternative drug for suppression of VT in patients with OMI.…”
Section: Discussionmentioning
confidence: 99%
“…This agent does, however, sometimes induce torsade de pointes 19) as a result of overdose. In our study, adverse events reported in association with nifekalant administration were marked QTc interval prolongation in two patients, one of whom experienced torsade de pointes.…”
Section: Discussionmentioning
confidence: 99%
“…Vol 45 No 4 In conclusion, intravenous infusion of NIF can be expected to be an effective, safe, and quick treatment for postoperative malignant VT refractory to class I agents with severe LV dysfunction under monitoring of QTc.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, NIF is particularly suited for treatment of VT in patients with severe LV dysfunction. 4) Class III agents increase cardiac refractory periods by lengthening the action potential duration (APD) and delaying recovery of excitability, and thus inhibit the re-entry circuit. But this prolongation of APD becomes less marked with an increase in heart rate.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In an experimental model of previous myocardial infarction nifekalant was effective against ventricular tachyarrhythmias, [15][16][17][18] and moreover, this effect was recently reported in patients with ischemic heart disease. [19][20][21][22][23] therefore, we investigated the efficacy and safety of nifekalant for the control of severe electrical storm in patients with an ICD.…”
mentioning
confidence: 99%